COMPOSITE MATERIALS - Khadzhieva S. S. (Bright Mind Publishing, 2025)
Chemistry and technology of composite, varnish and rubber materials consists of the creation of composite materials, their composition and effective technology. Chemical technology (high-molecular compounds) covers the areas of technology of high-molecular compounds, production, processing of polymers, polymer composite materials, organization of modern and safe production and management of it in the field of production and technical knowledge.
Keywords: Chemical technology, polymer, plastics, thermosetting plastics, thermoplastics, composite materials and innovative technologies.